Applications of microbial-induced carbonate precipitation: A state-of-the-art review - Yuze Wang; Charalampos Konstantinou; Sikai Tang; Hongyu Chen (Biogeotechnics)
Microbial-Induced Carbonate Precipitation (MICP) is a naturally occurring process whereby bacteria produce enzymes that accelerate the precipitation of calcium carbonate. This process is facilitated through various bacterial activities, including ureolysis, sulfate reduction, iron reduction, and denitrification. The application of MICP has been widespread in a range of engineering fields, such as geotechnical, concrete, environmental, and oil and gas engineering for soil stabilization, concrete remediation, heavy metal solidification, and permeability control. Numerous review papers have been published that summarize the mechanisms and properties associated with different MICP applications. The purpose of this review paper is to provide a comprehensive summary of the various engineering applications of MICP, along with the mechanisms, materials, and engineering properties associated with each application. By comparing the similarities and differences in MICP research progress across different engineering fields, this review aims to increase understanding of MICP, stimulate new research ideas, and accelerate the development of MICP techniques.